Analisis Faktor yang Memengaruhi Tarif Pajak Efektif Perusahaan - Reinhard Tavarel; Fanny Anggraeni (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The aim of this research is to obtain empirical evidence regarding the factors that influence effective tax rate in manufacturing companies listed on the Indonesia Stock Exchange. These factors are capital intensity ratio, inventory intensity ratio, leverage, intellectual capital, managerial ownership, profitability, and fiscal loss compensation. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. Purposive sampling method was used to obtained the sample. There were 81 companies that met the predetermined criteria so that the total data used as the research sample was 243 data. These variables were tested using multiple regression analysis. The results of this study indicate that the intellectual capital, profitability and fiscal loss compensation have an influence on effective tax rate. While the capital intensity ratio, inventory intensity ratio, leverage, and managerial ownership do not have an effect on effective tax rate.